Pengaruh Disiplin Kerja Dan Motivasi Kerja Terhadap Prestasi Kerja Pegawai Dinas Sosial Kabupaten Bima - Safira Safira; Khairul Amar (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
This study aims to determine the effect of work discipline and work motivation on the work performance of employees of the Bima District Social Service. This type of research is associative. The research instrument used in this study was a questionnaire with a Likert scale. The population used in this study were all employees who worked at the Bima Regency Social Service Office with a total of 73 employees and a total sample of 37 civil servants. Data collection techniques used in this study were observation, questionnaires, interviews and literature study. The data analysis technique used in this research is validity test, reliability test, classical assumption test, multiple linear regression analysis, multiple correlation coefficient, determination test, t test and f test. The results of the study show that partially or simultaneously the variables of work discipline and work motivation have a significant positive effect on the work performance of the employees of the Bima District Social Service.